1982
DOI: 10.1128/mcb.2.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a retrovirus as a eucaryotic vector transmitting the herpes simplex virus thymidine kinase gene.

Abstract: We investigated the feasibility of using retroviruses as vectors for transferring DNA sequences into animal cells. The thymidine kinase (tk) gene of herpes simplex virus was chosen as a convenient model. The internal BamHI fragments of a DNA clone of Moloney leukemia virus (MLV) were replaced with a purified BamHI DNA segment containing the tk gene. Chimeric genomes were created carrying the tk insert in both orientations relative to the MLV sequence. Each was transfected into TK-cells along with MLV helper vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(45 citation statements)
references
References 34 publications
(31 reference statements)
0
44
0
1
Order By: Relevance
“…Although initial reports from a number of laboratories described low levels of globin expression in transgenic mice comparable to that in in vitro experiments (12,25,42,47), one study (43) (14). High-level transcription of viral RNA requires the viral enhancer, and therefore, as expected, near normal levels of viral RNA are seen after differentiation of MEL cells infected with pSVX3(RO) but not with pSVX,Ben-.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial reports from a number of laboratories described low levels of globin expression in transgenic mice comparable to that in in vitro experiments (12,25,42,47), one study (43) (14). High-level transcription of viral RNA requires the viral enhancer, and therefore, as expected, near normal levels of viral RNA are seen after differentiation of MEL cells infected with pSVX3(RO) but not with pSVX,Ben-.…”
Section: Resultsmentioning
confidence: 99%
“…To date, these vectors have been used predominantly for transfer and expression of exogenous cDNA sequences under the control of viral transcriptional signals (17,20,32). In addition, several groups have reported the construction of recombinant genomes containing whole genomic gene sequences or minigenes [i.e., cDNA sequences flanked by promoter and poly(A) sites] (15, 16, 23, 24,33,40,42,48). Because it has been shown that a variety of genes contain regulatory sequences, not only 5' of the gene but also in introns (2,18,36) and intragenic sequences (8,52), we wished to determine whether, in general, intact genomic sequences could also be transferred to cells via retrovirus vectors and whether the sequences would be properly expressed within the context of an integrated provirus.…”
mentioning
confidence: 99%
“…Successful gene transfer by viral infection has been demonstrated for a variety of genes inserted into retroviral vectors. These genes include selectable markers (thymidine kinase [TK] [3,27,30,34] and hypoxanthine phosphoribosyltransferase [HPRT] [20]), the dominant selectable markers for neomycin resistance (neo) (10,14,16) and xanthineguanine phosphoribosyltransferase (gpt) (10,18,23), and also nonselectable genes linked to selectable markers (21). We have tested the utility of the mutant dihydrofolate reductase (DHFR; EC 1.5.1.3) gene as a potential dominant selectable marker in retroviral vectors.…”
mentioning
confidence: 99%
“…The favourite foreign gene has been the thymidine kinase (tk) gene of HSV, because expression of this gene can be selected for after infection or transfection of tk-cells. Wei et al (198l), Shimotohno & Temin (1981) and Tabin et al (1982) have used Harvey murine sarcoma virus, spleen necrosis virus and Moloney murine leukaemia virus, respectively, as vectors to construct recombinant genomes capable of transducing the HSV tk gene. The recombinant genomes thus produced are, like most strongly transforming viruses, replication-defective because the exogenous gene is inserted in place of one or more of the viral genes required for replication.…”
Section: Vectors For the Propagation Of Recombinant Genomes As Virionsmentioning
confidence: 99%